Pengembangan Kompetensi Profesional Guru Matematika melalui Lokakarya Penelitian Tindakan Kelas - Nasir, Rahma; Uncok Manigor Jokkas Siahaan; Ni Made Intan Kertiyani; Fajriani (FKIP Universitas Mataram, 2025)
One of the most effective strategies to improve mathematics teachers' professional competency is providing regular professional development workshops and training sessions for teachers. The aim of this study is to answer the following research questions: (1) How to design PD program for mathematics teachers in Indonesia through online workshop? (2) What are areas that need to be improved so that the program works as planned the next time? A “design research” method adopted for analyzing the process of PD program through collaboration CAR. The participant in this study were 24 mathematics teachers from 12 provinces. Data were collected through evaluation forms, focus group discussion, group meeting and learning logs, then the data were analyzed using grounded theory approach through the process of open, axial, and selective coding. 51% of participants considered the workshop to be very good, and 49% provided suggestions for improvement for further implementation. The two biggest factors to improve are adjusting the time to suit the participants and considering the technical issues that teachers might face. Based on the evaluation form each week, teachers considered that they need to join wokshop related to related to the Kurikulum Merdeka implementation, teaching media, ICT integration, and book publishing.